Clearance effect on the sheared edge characteristics of key chain cranioplasty plate in the punching process. Issue 1 (February 2021) - Lubis, Didin Zakariya; Suprayitno,; Asfani, Khoiruddin; Cholif Arrahman, Muhammad Baril
Abstract: Punching process is a process to cut sheet metal by pressing the workpiece until it exceeds the elastic limit of the material. In this study, the researcher used the finite element method as a solution to a problem during the manufacturing process. This research simulated the punching process, particularly hole-making, in keychain cranioplasty product to obtain smoothest sheared edge characteristics by optimising the clearance amount variations. The product had 1.53 mm diameter and 0.6 mm thickness of titanium alloy plate. The analysis was performed using the finite element method with the support of ANSYS Explicit Dynamic software. During the punching process, the punching speed was 2600 mm/min. The results showed that reductions in clearance, below 2.5% clearance, produced rougher sheared edge. The higher clearance produce rougher sheared edge. The 2.5% clearance was the standard for a right sheared edge to make a hole in the keychain cranioplasty plate with 0.6 mm thickness.